Adenosine Receptors in Health and Disease - Wilson, Constance N.; Mustafa, S. Jamal; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
Since their discovery approximately 25 years ago, adenosine receptors have now emerged as important novel molecular targets in disease and drug discovery. These proteins play important roles in the entire spectrum of disease from inflammation to immune suppression. Because of their expression on a number of different cell types and in a number of different organ systems they play important roles in specific diseases, including asthma, rheumatoid arthritis, Parkinson$1 (Bs disease, multiple sclerosis, Alzheimer$1 (Bs disease, heart disease, stroke, cancer, sepsis, and obesity. As a result of intense investigations into understanding the molecular structures and pharmacology of these proteins, new molecules have been synthesized that have high specificity for these proteins and are now entering clinical trials. These molecules will define the next new classes of drugs for a number of diseases with unmet medical needs.s
to Adenosine Receptors as Therapeutic Targets -- A1 Adenosine Receptor Antagonists, Agonists, and Allosteric Enhancers -- Recent Developments in Adenosine A2A Receptor Ligands -- Recent Developments in A2B Adenosine Receptor Ligands -- Medicinal Chemistry of the A3 Adenosine Receptor: Agonists, Antagonists, and Receptor Engineering -- Adenosine Receptors and the Heart: Role in Regulation of Coronary Blood Flow and Cardiac Electrophysiology -- Adenosine Receptors and Reperfusion Injury of the Heart -- Adenosine Receptors and Inflammation -- A1 Adenosine Receptor: Role in Diabetes and Obesity -- A3 Adenosine Receptor: Pharmacology and Role in Disease -- Adenosine Receptors and Asthma -- Adenosine Receptors, Cystic Fibrosis, and Airway Hydration -- Adenosine Receptors in Wound Healing, Fibrosis and Angiogenesis -- Adenosine Receptors and Cancer -- Adenosine Receptors and the Kidney -- Adenosine Receptors and the Central Nervous System -- Adenosine Receptors and Neurological Disease: Neuroprotection and Neurodegeneration -- Adenosine A2A Receptors and Parkinson$1 (Bs Disease -- Adenosine Receptor Ligands and PET Imaging of the CNS.s
Keywords: Medicine; Human physiology; Pharmacology; Cell biology; Biomedicine; Pharmacology/Toxicology.; Human Physiology; Cell Biology; Electronic books